1999
DOI: 10.1055/s-1999-13968
|View full text |Cite
|
Sign up to set email alerts
|

A Sesquiterpene, Dehydrocostus Lactone, Inhibits the Expression of Inducible Nitric Oxide Synthase and TNF-α in LPS-Activated Macrophages

Abstract: Nitric oxide (NO) and tumor necrosis factor alpha (TNF-alpha) are the major mediators produced in activated macrophages which contribute to the circulatory failure associated with septic shock. A sesquiterpene lactone compound (dehydrocostus lactone) isolated from the medicinal plant, Saussurea lappa, inhibited the production of NO in lipopolysaccharide (LPS)-activated RAW 264.7 cells by suppressing inducible nitric oxide synthase enzyme expression. This compound also decreased the TNF-alpha level in LPS-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 7 publications
0
48
0
1
Order By: Relevance
“…The observed protective effects of Sl.Cr might be due to the reported facts of its identifi ed phytochemicals. The compounds from Saussurea lappa root like costunolide and dehydrocostus lactone (Lee et al, 1999), reynosin and santamarine (Cho et al, 1998) and saussureamine (Matsuda et al, 2003) have shown inhibitory effect on expression of TNF-α and NO, respectively, from activated macrophages. Calcium channel blockers have shown hepatoprotection (Farghali et al, 2000) and we have recently identifi ed calcium channel blocking (CCB) constituents in Saussurea lappa (Gilani et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The observed protective effects of Sl.Cr might be due to the reported facts of its identifi ed phytochemicals. The compounds from Saussurea lappa root like costunolide and dehydrocostus lactone (Lee et al, 1999), reynosin and santamarine (Cho et al, 1998) and saussureamine (Matsuda et al, 2003) have shown inhibitory effect on expression of TNF-α and NO, respectively, from activated macrophages. Calcium channel blockers have shown hepatoprotection (Farghali et al, 2000) and we have recently identifi ed calcium channel blocking (CCB) constituents in Saussurea lappa (Gilani et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages play a central role in mediating a number of different immunopathological phenomena during inflammation by the overproduction of inflammatory mediators, known as Nitric oxide (NO) and prostaglandins (PGs) (Ricciotti et al 2011;Lee et al 1999). Therefore, the inhibition of NO and PGE2 production may have potential therapeutic value when related with inflammation.…”
Section: The Phenolic Compound Content and Bioactivity Of Cb-ros Mixtmentioning
confidence: 99%
“…NO plays an important role in the inflammatory process, and an inhibitor of NO release may be considered as a therapeutic agent in the inflammatory diseases (Lee et al, 1999) Results of the anti-inflammatory test (Table 5) indicated that the total extraction, petroleum ether fraction and ethyl acetate fraction had different inhibitory activity. Both n-butanol and water fractions showed no inhibitory activity (IC 50 >100 μg/mL).…”
Section: Anti-inflammatory Activity Of W Indicamentioning
confidence: 99%